Effects of monoolein-based cubosome formulations on lipid droplets and mitochondria of HeLa cells. Issue 4 (13th May 2015) - Falchi, Angela Maria; Rosa, Antonella; Atzeri, Angela; Incani, Alessandra; Lampis, Sandrina; Meli, Valeria; Caltagirone, Claudia; Murgia, Sergio
Graphical Abstract: Abstract: Despite the remarkable development of nanoparticles for different purposes, relatively little is known about their interaction with biological systems and individual cells. Here the effects of two monoolein-based cubosome formulations stabilized by Pluronic F108 and F127 were investigated against HeLa cells. Microscopy analysis on living cells loaded with organelle-specific fluorescent probes was performed to assess the formation of cytoplasmic lipid droplets after nanoparticle treatment. Mitochondrial membrane potential and mitochondrial ROS generation were also investigated in relation to the capability of the accumulated lipids to affect mitochondrial functions. Values of the main cellular unsaturated fatty acids were also measured to assess cell lipid profile modulation. Results from this study show that the uptake of both cubosome formulations induced modification of the cell lipid profile, lipid droplet accumulation, mitochondrial hyperpolarization and mitochondrial ROS generation. These results shed some light on the influence exerted by monoolein-based cubosome formulations on subcellular organelles and their possible adverse effects on cell functions.